Byzantine Ideas of Persia, 650-1461 - Shukurov, Rustam (Global Histories Before Globalisation, 2024)
This book offers a study into the perceptions of ancient and medieval Iran in the Byzantine Empire, as well as the effects of Persian culture upon Byzantine intellectualism, society, and culture. Byzantine Ideas of Persia, 650-1461 focuses on the place of ancient Persia in Byzantine cultural memory, both in the "religious" and the "secular" sense. By analysing a wide range of historical sources - from church literature to belles-lettres - this book provides an examination of the place of ancient Persia in Byzantine cultural memory, as well as the place and function of Persian motifs in the Byzantine mentality. Additionally, the author uses these sources to analyse thoroughly the knowledge Byzantines had about contemporary Iranian culture, the presence of ethnic Iranians and the circulation and usage of the Persian language in Byzantium. Finally, this book discusses the importance and influence of Iranian science on Byzantine scholars. This book will appeal to scholars and students interested in Byzantine and Iranian History, particularly in reference to the cross-cultural and social influence of the two societies during the Middle Ages.